Malignant neoplasia of sigmoid colon in incarcerated left inguinal hernia: case report - de Almeida Barbosa, Cirênio; Almeida da Silva, Rafaela; José da Cunha, Adéblio; Soares dos Santos, Ronald; Chaves Moreira, Weber; Martins Neves, Peterson; Luiz Vieira Tannús, Cláudio (Seven Editora, 2023)
Colon carcinoma in an incarcerated inguinal hernia is an uncommon finding. Few cases are reported in the literature. It usually appears in the left inguinal hernias and includes part of the sigmoid colon. Palpation of a tumor in a previously non-existent hernia and the presence of bowel symptoms help with the diagnosis. An incarcerated inguinoscrotal hernia is noted as a mass in the inguinal and scrotal region, which cannot reduce spontaneously. It is more common in men, infants, and the elderly. The presence of an intermittent mass in the inguinal region is the classic picture of patients with hernia. If it evolves to incarceration, it may present vomiting, colic pain, abdominal distension, and stop in the elimination of feces and gases. The diagnosis of an incarcerated hernia is usually made through palpation on physical examination. However, in some cases, computed tomography of the abdomen with contrast is used, or even ultrasound of the entire abdomen. An inguinal hernia may surprise the surgeon at the time of surgery. The presence of the sigmoid colon, in an inguinal hernia, without associated alterations, is a rare entity, and alterations such as colon cancer or even sigmoid diverticular disease are usually found. A rare case is presented in which the hernial sac contains the sigmoid colon with the onset of ischemic suffering, culminating in a sigmoidectomy with lymphadenectomy and exteriorization of the proximal loop using the Hartman technique. DOI: https://doi.org/10.56238/devopinterscie-137